Aluminosilicat mao quản trung bình từ cao lanh không nung. Phần 1 – Nghiên cứu chuyển hóa cao lanh không nung thành vật liệu mesopore chứa cấu trúc zeolit loại MFI và BEA trong môi trường kiềm. - Hảo, Phan Minh; Đôn, Tạ Ngọc; Linh, Nguyễn Thị; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2012)
Mesoporous aluminosilicate materials assembled from zeolite type MFI and BEA seeds were synthesized from kaolin in the presence of cetyltrimethylamoniumbromua. The results obtained from SAXS, nitrogen adsorption isotherm, TEM, and IR exhibited that the materials have ordered hexagonal mesostructures with average pore size of 39 Å, wall thickness of 7 Å, BET surface area of 606 m2/g and porous volume of 0.82 cm3/g. The results from XRD also indicated that the conversion of kaolin into mesopore was not complete.